2021
DOI: 10.1177/10497323211054058
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Data Sharing: Participant Understanding, Motivation, and Consent

Abstract: Expectations to share data underlying studies are increasing, but research on how participants, particularly those in qualitative research, respond to requests for data sharing is limited. We studied research participants’ willingness to, understanding of, and motivations for data sharing. As part of a larger qualitative study on abortion reporting, we conducted interviews with 64 cisgender women in two states in early 2020 and asked for consent to share de-identified data. At the end of interviews, we asked p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…Moreover, senior faculty in the social sciences are not necessarily familiar with best practices in information security and may sometimes provide outdated advice. Finally, and most relevant to the possibilities of future use and sharing of qualitative data is that advice by senior researchers, who were rarely subject to data-sharing mandates, may be overly restrictive and prevent future sharing of data, e.g., due to lack of consent to data sharing by participants (see, e.g., VandeVusse, Mueller, and Karcher 2022;Mozersky et al 2020 on consent for data sharing in qualitative research).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, senior faculty in the social sciences are not necessarily familiar with best practices in information security and may sometimes provide outdated advice. Finally, and most relevant to the possibilities of future use and sharing of qualitative data is that advice by senior researchers, who were rarely subject to data-sharing mandates, may be overly restrictive and prevent future sharing of data, e.g., due to lack of consent to data sharing by participants (see, e.g., VandeVusse, Mueller, and Karcher 2022;Mozersky et al 2020 on consent for data sharing in qualitative research).…”
Section: Discussionmentioning
confidence: 99%
“…The respondents of their survey reported key concerns about protecting data that may be sensitive and that they had not obtained permission from the participants to share data. A recent study supports these concerns: VandeVusse et al [91] found that participants in qualitative studies volunteer to share data to be helpful. However, their participants misunderstood "sharing" as disseminating research findings instead of sharing the interview transcripts [91].…”
Section: Transparency Of Datamentioning
confidence: 95%
“…A recent study supports these concerns: VandeVusse et al [91] found that participants in qualitative studies volunteer to share data to be helpful. However, their participants misunderstood "sharing" as disseminating research findings instead of sharing the interview transcripts [91]. HCI research has looked into challenges in Research Data Management [34,35] and has come up with an innovative approach to facilitate sharing despite these challenges [63].…”
Section: Transparency Of Datamentioning
confidence: 95%
“…Public qualitative data could potentially be beneficial when individuals or groups are particularly difficult to access (Fielding, 2004) or groups that might face trauma from multiple rounds of research participation (Ruggiano & Perry, 2019). Some research has revealed participants are generally willing to allow researchers to archive and share their qualitative data (e.g., Cummings et al, 2015;Mozersky et al, 2020;VandeVusse et al, 2022) out of a desire to help others and improve research.…”
Section: Common Concerns About the Quantitative Open Science View Of ...mentioning
confidence: 99%